Dietary Fiber Intake and Risk of Chronic Obstructive Pulmonary Disease: A Prospective Cohort Study of Men. Issue 2 (March 2018) - Kaluza, Joanna; Harris, Holly; Wallin, Alice; Linden, Anders; Wolk, Alicja
Abstract : Background: The limited literature suggests that dietary fiber intake from whole grains, fruits, and vegetables is negatively associated with chronic obstructive pulmonary disease (COPD) via fiber's anti-inflammatory properties. Therefore, we investigated the association between total fiber and fiber sources and risk of COPD in the population-based prospective Cohort of Swedish Men (45, 058 men, ages 45–79 years) with no history of COPD at baseline. Methods: Dietary fiber intake was assessed with a self-administered questionnaire in 1997 and was energy adjusted using the residual method. Cox proportional hazard regression models were used to estimate hazard ratios (HRs) with 95% confidence intervals (95% CIs) adjusted for potential confounders. Results: During a mean follow-up of 13.1 years (1998–2012), 1, 982 incident cases of COPD were ascertained via linkage to the Swedish health registers. A strong inverse association between total fiber intake (≥36.8 vs. <23.7 g/day) and COPD was observed in current smokers (hazard ratio [HR] = 0.54; 95% confidence interval [CI] = 0.43, 0.67) and ex-smokers (HR = 0.62; 95% CI = 0.50, 0.78) but not in never smokers (HR = 0.93; 95% CI = 0.60, 1.45; P interaction = 0.04). For cereal fiber, HRs for highest versus lowest quintile were 0.62 (95% CI = 0.51, 0.77; P trend < 0.001) in current smokers and 0.66 (95% CI = 0.52, 0.82; P trend < 0.001) in ex-smokers; for fruit fiber, the HR was 0.65 (95% CI = 0.52, 0.81; P trend < 0.001) in current smokers and 0.77 (95% CI = 0.61, 0.98; P trend = 0.17) in ex-smokers; and for vegetable fiber, it was 0.71 (95% CI = 0.57, 0.88; P trend = 0.003) in current smokers and 0.92 (95% CI = 0.71, 1.19; P trend = 0.48) in ex-smokers. Conclusions: Our findings indicate that high fiber intake was inversely associated with COPD incidence in men who are current or ex-smokers. Abstract : Supplemental Digital Content is available in the text.